An Integrated Analysis of mRNAs and miRNAs Microarray Profiles to Screen miRNA Signatures Involved in Nasopharyngeal Carcinoma. (25th September 2020) - Liu, Lei; Wang, Hailing; Yan, Chaohui; Tao, Shudong
Objective: We aim to identify several microRNAs (miRNAs/miRs)-messenger RNAs (mRNAs) biomarkers correlated to nasopharyngeal carcinoma (NPC) based on an integrated analysis of miRNA and mRNAs microarray expression profiles. Methods: The available mRNA and miRNA microarray datasets were retrieved from Gene Expression Omnibus (GEO) database according to pre-determined screening criteria. Differentially expressed miRNA and mRNAs (DEmiRNAs and DEmRNAs) were extracted between NPC and noncancerous nasopharyngeal tissues. The target genes of DEmiRNAs were predicted with miRTarBase followed by the construction of DEmiRNAs-target DEmRNAs network, and functional analyses were performed. The DEmiRNAs expressions were validated and the performance of these DEmiRNAs was assessed by the area under the curve (AUC) values. Finally, the correlations between DEmiRNAs and specific clinical factors were analyzed. Results: There were 1140 interaction pairs (including let-7d/f- MYC / HMGA2 and miR-452- ITGA9 ) in DEmiRNAs-target DEmRNAs network. The GO annotation analysis showed that several genes such as MYC, HMGA2 and ITGA9 primarily participated in cellular process. KEGG analysis showed that these targets were associated with cell cycle and cancer-related pathways. Down-regulated let-7(-d and –f) and up-regulated miR-452 were verified in datasets. The AUC values of these 3 DEmiRNAs (let-7d, let-7-f and miR-452) was 0.803, 0.835 and 0.735, respectively. Besides, miR-452 was significantly related to survival rate of NPC patients. Conclusion: The findings implied let-7d/f- MYC / HMGA2 and miR-452- ITGA9 might be promising targets for the detection and treatment of NPC.